2002
DOI: 10.1016/s0002-9440(10)64912-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cyclooxygenase 2 Is an Independent Prognostic Factor in Human Ovarian Carcinoma

Abstract: Cyclooxygenase-2 (COX-2) is the rate-limiting enzyme in prostanoid biosynthesis and is involved in tumor progression. We investigated expression of COX-1 and COX-2 in cell lines and tumors from ovarian carcinomas. Expression of COX-2 mRNA and protein was detectable in three of five ovarian carcinoma cell lines and was inducible by interleukin-1␤ or phorbolester in a subset of cell lines. Prostaglandin E 2 (PGE 2 ) production could be inhibited by the selective COX-2 inhibitor NS-398. In malignant ascites of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
3
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 43 publications
12
137
3
5
Order By: Relevance
“…Decreased sensitivity to chemotherapy and poor prognostic outcome has been associated with ovarian carcinomas expressing COX-2 (24). However, it has been shown that COX-2 is only expressed in a subset of ovarian carcinomas (25).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased sensitivity to chemotherapy and poor prognostic outcome has been associated with ovarian carcinomas expressing COX-2 (24). However, it has been shown that COX-2 is only expressed in a subset of ovarian carcinomas (25).…”
Section: Discussionmentioning
confidence: 99%
“…15 Immunohistochemical staining of COX-2 was performed according to standard procedures as previously described. 16 To evaluate the specificity of the COX-2 antibody (Cayman Chemical, Ann Arbor, MI, USA) we and others have already performed blocking experiments with the COX-2 blocking peptide (Cayman Chemicals) according to the manufacturer's instructions. 15 In addition, we used control tissue and cell lines for control of immunohistochemical staining procedures.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Par ailleurs, un rôle important des prostaglandines endoperoxydases COX1 et COX2, de la prostaglandine E2 (PGE2) et de son enzyme de synthèse la prostaglandine E synthase (PGES), a été démontré dans la tumorigenèse ovarienne [42][43][44]. Nos études récentes ont montré une forte expression des partenaires de la voie de signalisation embryonnaire mâle L-PGDS/SOX9 dans des biopsies de tumeurs ovariennes humaines de différents types histologiques [45] ( Figure 3A).…”
Section: Revuesunclassified